Quantification of phenols, anthocyanins and sensory characterization of nibs and liquor of five cocoa varieties, in two fermentation systems - Ordoñez, Elizabeth S. (2020)
Perú boasts a wide diversity of fine aroma cocoa that merits quantifying its total phenols, anthocyanins, and characterize sensory the liquor and nibs of cacao, in two fermentation systems: traditional and micro-fermentation. The studying samples were “Chuncho”, Señorita variety, Achoccha, Pamuco and Común, and SHU-1 variety. For the quantification of total phenols was prepared a hydroalcoholic extract (100mg/mL). To the sensory characterization were chosen thirteen attributes whose results were subjected to multivariate analysis using the principal components method. The amount of total phenols was lower in the liquor compared to cocoa nibs, except in the microfermentation of Señorita and Achoccha variety, and in the traditional fermentation of Señorita variety; being the anthocyanin content higher compared to nibs. The cocoa liquor of Achoccha, Común and Señorita varieties in micro-fermentation developed typical sensory notes of fine cocoas, with important correlations between bitterness/astringency (0.90) and between astringency/fresh fruit (-0.64). The nibs showed fine cocoa profiles with high correlation between aroma/spices (0.72) and intermediate between defects/floral (-0.61), considering to SHU-1 variety, like a fine aroma cocoa.